Psychocorrection and optimal pharmacotherapy in anxiety-phobic syndrome. - Karakhonova, Sarvinoz (Psychosomatic Medicine and General Practice, 2019)
Background. The article presents methods of detection and ways of correction of psychosomatic disorders among patients suffering from anxiety and phobic syndrome. These studies have shown that among patients with anxiety-phobic syndrome of psychosomatic disorders are most pronounced anxiety, phobia, fear, panic. Therefore, in addition to the basic therapy in patients with anxiety-phobic syndrome, psychotherapy was used, which led to early recovery, effective treatment, as well as lengthening the period of remission. The purpose. Although today some scientific studies are conducted on the methods of treating patients with anxiety-phobic syndrome, several questions about effective treatment methods of psychodiagnostics and psychocorrections are still unknown. According to various authors, anxiety-phobic syndrome is 38-43% in the structure of neurological diseases. The study was aimed at researching the levels of anxiety in anxiety-phobic syndrome and to improve their psychological correlation. Materials and methods. Materials for the study were collected from the first and second departments of the clinic of Tashkent Medical Academy (TMA). As a primary research material, 46 patients who were treated with a diagnosis of Psychosomatic syndrome - a predominance of anxiety were taken. Patients are aged between 25-40years and the average age is 32.5±2.3. The diagnosis was based on complaints, Anamnesis, objective and neurological status, as well as paraclinical data when patients came to the clinic for hospital treatment. Mental disturbances, objective and neurological status were evaluated through medical psychological tests with the help of recommendation of medical psychological questionnaire by Ibodullaev Z.R.(patent №001031) Results. Anxiety level sare detected through the HADS scale: in the first group patients had light (mild) level among 4 patients, medium level among 7 patients, high-level anxiety indicators in 9 patients; the second group patients were found light level in 6 patients, medium level in 8 patients, high level in 8 patients (Р<0,05). Conclusion. Based on these results, it is recommended to use psychopharmacotherapeutic treatment and cognitive-behavioral psychotherapy, adding to the basis of the treatment of patients with anxiety-syndrome in neurosis.